2013
DOI: 10.1097/mpg.0b013e31826f2b8c
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Outcomes for Children With Nonalcoholic Fatty Liver Disease Over Time and Compared With Obese Controls

Abstract: Children with NAFLD have higher levels of depression than obese controls. Outcomes did not improve with standard care. Larger longitudinal studies and appropriate interventions are required in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 15 publications
2
49
0
1
Order By: Relevance
“…[24] There is also growing evidence that children and adolescents with NAFLD have a higher rate of psychological distress compared with healthy or obese controls. [25,26] Furthermore, in the present research, occupational stress was demonstrated to be a risk factor for NAFLD among Chinese police officers.…”
Section: Discussionsupporting
confidence: 54%
“…[24] There is also growing evidence that children and adolescents with NAFLD have a higher rate of psychological distress compared with healthy or obese controls. [25,26] Furthermore, in the present research, occupational stress was demonstrated to be a risk factor for NAFLD among Chinese police officers.…”
Section: Discussionsupporting
confidence: 54%
“…Another study on 48 children and adolescents with NAFLD between 8 and 18 years found higher levels of depression compared to obese children and adolescents without NAFLD. 102 In addition, more frequent emotional and behavioral problems have been noted in children with NAFLD compared to healthy controls. 97 There are important questions that remain regarding how much the psychosocial problems observed are due to NAFLD itself versus the role of obesity and/or other unmeasured factors.…”
Section: Associated Co-morbidities Of Nafldmentioning
confidence: 99%
“…Fatigue, trouble sleeping, and sadness were the symptoms that accounted for nearly half of the variance in quality of life scores compared to controls [24]. In a study of psychosocial outcomes in children with NAFLD, children with NAFLD had higher levels of depression compared to obese controls [25]. Children with NAFLD may have a substantial psychological burden and disease management should take potential psychosocial co-morbidities into account to provide patient-centered care.…”
Section: Introductionmentioning
confidence: 99%